Managing Carbon, Managing Futures: A Study of Sociotechnical Imaginaries in the Rollout of CCUS in Denmark - Brix Georgsen,Kara (Master Thesis Series in Environmental Studies and Sustainability Science, 2025)
Carbon capture utilization and storage (CCUS) is set to play a key role in decarbonization. Most of the technologies are yet to be seen on commercial scale. Denmark is in the process of establishing some of the first large-scale CCUS value-chains. Through a combination of document analysis and interviews, I study the ideas driving the current roll-out of CCUS in Denmark. To do this, I make use of the analytical concept of sociotechnical imaginaries. Through my work, I find that CCUS is mobilised as a necessary tool for halting climate change. It is also envisioned as a profitable business adventure and with potential to secure Denmark’s image as a climate frontrunner. This leads me to discuss how the rollout of CCUS is driven by an approach to climate mitigation which centres technological development and market-driven mechanisms. I conclude that, while CCUS might be deemed necessary for industrial decarbonisation, the technologies are unlikely to foster wide-reaching change, thus it remains key to continuously scrutinize its role in climate mitigation and the construction of more climate-friendly societies.
Keywords: CCUS; industrial decarbonisation; carbon infrastructure; climate change mitigation; sociotechnical imaginaries; ecomodernism; sustainability science